2021
DOI: 10.2147/cmar.s307920
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Preoperative Controlling Nutritional Status Score Combined with Fibrinogen–Albumin Ratio in Postoperative Local Recurrence-Free Survival of Patients with Retroperitoneal Liposarcoma

Abstract: Background Previous studies have shown that nutrition and systemic inflammation plays an essential role in the development of soft tissue sarcoma. However, few studies have explored the association of clinicopathologic features and local recurrence with nutritional and inflammatory markers in retroperitoneal liposarcoma (RPLS). This study sought to evaluate the prognostic value of the preoperative nutritional and inflammatory markers for local recurrence-free survival (LRFS) among surgical RPLS pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Also interesting is the finding that tumor size is an independent risk factor for CSS, not for OS. The 5-cm threshold used in the AJCC staging system is still limited about the value for RPLs because such small RPLs are uncommon in the present and other international studies ( 17 , 25 , 35 , 43 ). Meanwhile, several studies proposed that the optimal threshold in tumor sizes should be revised upward to 10 cm ( 25 , 36 ).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Also interesting is the finding that tumor size is an independent risk factor for CSS, not for OS. The 5-cm threshold used in the AJCC staging system is still limited about the value for RPLs because such small RPLs are uncommon in the present and other international studies ( 17 , 25 , 35 , 43 ). Meanwhile, several studies proposed that the optimal threshold in tumor sizes should be revised upward to 10 cm ( 25 , 36 ).…”
Section: Discussionmentioning
confidence: 72%
“…The finding is consistent with previous research showing that increased survival is directly associated with better histologic grade ( 35 , 37 40 ). Furthermore, previous analyses showed that completeness of resection is another important prognostic factor ( 17 , 40 43 ). We also found that the prognosis of patients who underwent resection was significantly better than that of patients without surgical resection, especially that of patients with radical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen, acted as an important acute-phase protein, is closely associated with coagulation cascade reaction, tumor immune, and systemic inflammation. 28 Notably, fibrinogen was able to serve as a cytoskeleton to support the extracellular matrix of tumors for facilitating tumor angiogenesis and amplifying tumor cell adhesion and invasion, which might be the implying reasons that the level of fibrinogen is associated with poor prognosis with malignancies. 29 Furthermore, albumin acts as an important protein in body, commonly reflects the nutritional status of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the peripheral blood platelet and fibrinogen increased significantly in patients with PS, while hemoglobin and albumin decreased significantly in patients with PS. Previous studies found that the peripheral blood platelet and fibrinogen are significantly related to the progress of malignant tumors ( 28 30 ), while the development of malignancies is related to the decrease in the hemoglobin and albumin ( 31 , 32 ). Thus, these changes may contribute to the progress of RPS as well.…”
Section: Discussionmentioning
confidence: 99%